ASSOCIATION OF SEROPOSITIVITY FOR CMV IGM AND IGG WITH ADVERSE PREGNANCY OUTCOME - Amna, Ambreen; Nadeem, Farkhunda; Fahim, Amin; Jatoi, Altaf Hussian; Abbas, Kanwal; Anas, Sumayya (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the prevalence of antibodies against cytomegalovirus and their association with adverse pregnancy outcome in women, at Isra University Hospital Hyderabad. Study Design: Cross-sectional study. Place and Duration of Study: Department of Gynaecology & Obstetrics, Isra University Hospital (IUH) Hyderabad, from Jan to Jun 2018. Methodology: Cytomegalovirus IgM and IgG antibodies in 305 women of reproductive age group were measured using the Enzyme Linked Fluorescent Assaysystem kit. Results: The combined positivity of anti cytomegalovirus IgG and IgM antibodies was 93 (30.40%). About 37 (37.37%) and 28 (34.14%) women were found to be seropositive for cytomegalovirus antibodies who had history of spontaneous miscarriage and recurrent miscarriages respectively. Conclusion: Higher association of seropositivity for cytomegalovirus IgM and IgG with bad obstetrical history and low economy was found.